Using design thinking to cultivate the next generation of female STEAM thinkers - Kijima, Rie; Yang-Yoshihara, Mariko; Maekawa, Marcos Sadao (International Journal of STEM Education, 2021)
Background Countries around the world have struggled to implement education policies and practices to encourage more female youths to pursue Science, Technology, Engineering, and Mathematics (STEM). This has resulted in a persistent and sizeable gender gap in science and mathematics subjects in some countries. Using mixed-methods sequential explanatory design, this paper explores an educational intervention—specifically, a 3-day design thinking workshop—in Japan, designed to change female youths’ perceptions regarding STEM topics. Framed using a constructivist approach to learning, the workshops aimed to engender creative confidence, empathy, and global competence among youths. Results The findings show that female youths who participated in the workshop had increased interest in engineering, greater creative confidence, more positive perceptions of STEM, higher levels of empathy and pro-social factors, and a more varied outlook on career options. We argue that this short intervention had a strong influence on the female youths’ mindsets, self-images, and perceptions of STEM. Conclusion This study provides empirical support that a short intervention can produce positive change in how female youths relate to STEM. In gendered societies, an innovative method like design thinking has the potential to revitalize education curriculum in ways that spur female youths’ confidence and creativity, enabling them to imagine a career in the field of STEM.